Design and performance analysis of low phase noise LC-voltage controlled oscillator - Ramchandra Gurjar; Deepak Kumar Mishra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Voltage controlled oscillator (VCO) offers the radio frequency (RF) system designer a freedom to select the required frequency. Today’s wireless communication system imposes a very stringent requirement in terms of phase noise generated in VCO. This study presents an inductive source degeneration technique to improve the phase noise performance of the inductance-capacitance (LC)-VCO. Double cross-coupled topology has been chosen for the proposed VCO. The post layout simulations with the parasitic resistance, inductance, capacitance (RLC) extracted view is carried out with united microelectronics corporations (UMC) 0.18 µm process by spectre simulator of cadence tools. The proposed VCO provides a phase noise of -124.3 dBc/Hz @ 1 MHz. The tuning range obtained is 19.87% with a centre frequency of 2.46 GHz which makes it suitable for industrial, scientific, and medical (ISM) band applications. It consumes a power of 2.10 mW. Also, a good figure of merit of -189 is achieved. The total layout area occupied is 477×545 µm2.